(untitled) (Journal of Science and Technology, 2022)
Improved health promotes socio-economic mobility, and in turn, attenuates predispositions to illnesses that culminate in impairments. This research investigated access to health facilities by persons with mobility impairments through physical audits using universal design principles as indicators. Subsequently, a survey and interviews were conducted with persons with mobility impairments to explore their spatial experiences with respect to transportation, movements, ac-cess and utilization. The results suggest that, despite the passage of the Disability Act (715) near-ly 15 years ago, the mobility impaired still encounter multiple physical and psychological barri-ers which impede access and utilization of health facilities with wide-ranging implications. These outcomes, reflect not only the lack offunding for retrofitting, but largely ingrained socie-tal perceptions about disability which invariably feed into policy in the production of public spaces. The research calls for a deeper introspection through disability awareness and educa-tional campaigns, an integrated approach to health policy and spatial planning, a review of the Disability Act to address its weaknesses and the passage of subsidiary legislations to spell out the rights, obligations and liabilities of health providers and built environment professionals.